The Influence of Earning Per Share, Price Earnings Ratio, and Price to Book Value toward Price of Stok of Coal Mining Companies Listed in the Indonesia Stock Exchange During 2014-2018 - Rr. Jean Brebeuf Iryani Andamari; Caecilia Wahyu Estining Rahayu; Ima Kristina Yulita (Soegijapranata Catholic University, 2021)
Company's financial performance is a factor considered by investors in investing. This study aims to determine the effect of Earning per Share (EPS), Price Earnings Ratio (PER), and Price to Book Value (PBV) on stock price. Eight coal mining companies listed in the Indonesia Stock Exchange (IDX) in 2014-2018 were taken for the samples of this research using purposive sampling technique. Multiple linear regression was used to analyze the data. The results show that (1) EPS, PER, and PBV simultaneously have a significant effect on stock price with a significance value of 0.000; (2) EPS and PBV partially have a significant effect on stock price with a significance value of 0.000 and 0.006 respectively. EPS, PER, and PBV can explain variation of the stock price of the coal companies listed in the IDX in 2014-2018 as much as 88.5%. The results of this study is expected to provide recommendations for investors in choosing stocks of coal mining company with good performance based on EPS and PBV ratios.